Local Insect Availability Partly Explains Geographical Differences in Floral Visitor Assemblages of Arum maculatum L. (Araceae) - Laina, Danae; Gfrerer, Eva; Scheurecker, Valerie; Fuchs, Roman; Schleifer, Marielle; Zittra, Carina; Wagner, Rüdiger; Gibernau, Marc; Comes, Hans Peter; Hörger, Anja C.; Dötterl, Stefan (Frontiers in Plant Science, 2022)
Geographical variation in abundance and composition of pollinator assemblages may result in variable selection pressures among plant populations and drive plant diversification. However, there is limited knowledge on whether differences in local visitor and pollinator assemblages are the result of site-specific strategies of plants to interact with their pollinators and/or merely reflect the pollinator availability at a given locality. To address this question, we compared locally available insect communities obtained by light trapping with assemblages of floral visitors in populations of Arum maculatum (Araceae) from north vs. south of the Alps. We further investigated whether and how the abundance of different visitors affects female reproductive success, and examined the pollen loads of abundant visitors. Local insect availability explained inter-regional differences in total visitor abundance, but only partly the composition of visitor assemblages. Northern populations predominantly attracted females of Psychoda phalaenoides (Psychodidae, Diptera), reflecting the high availability of this moth fly in this region. More generalized visitor assemblages, including other psychodid and non-psychodid groups, were observed in the south, where the availability of P. phalaenoides/Psychodidae was limited. Fruit set was higher in the north than in the south but correlated positively in both regions with the abundance of total visitors and psychodids; in the north, however, this relationship disappeared when visitor abundances were too high. High pollen loads were recorded on both psychodids and other Diptera. We demonstrate for the first time that the quantitative assessment of floral visitor assemblages in relation to locally available insect communities is helpful to understand patterns of geographical variation in plant–pollinator interactions. This combined approach revealed that geographical differences in floral visitors of A. maculatum are only partly shaped by the local insect availability. Potential other factors that contribute to the geographical pattern of visitor assemblages may include the region-specific attractiveness of this plant species to flower visitors and the population-specific behaviour of pollinators.